Atheroprotective Effects and Mechanisms of Postmarketing Chinese Patent Formulas in Atherosclerosis Models: A Systematic Review. (27th November 2021) - Chen, Shiqi; Wu, Xiaoxiao; Li, Tong; Li, Yang; Wang, Baofu; Cheng, Weiting; Teng, Yu; Yang, Jingjing; Meng, Hui; Wang, Lei; Lu, Ziwen; Jiang, Yangyang; et al.
Abstract : Background . Some postmarketing Chinese patent formulas have been widely used to treat atherosclerosis (AS) and play critical roles in Chinese healthcare. However, the usage of these herbs is yet controversial due to unclear effects and lack of understanding of the mechanism of action. With the modernization of traditional Chinese formulas, we are to elucidate the atheroprotective properties of these remedies from successful postmarketing experiments in vivo . Methods . In this systematic review, we critically searched the databases, applied stringent criteria, assessed the methodological quality, and examined the current evidence in vivo . Results . Consequently, 60 studies were included in the present qualitative synthesis. Data on models, high-fat diet, intervention time, outcome measures, efficacy, and mechanisms were collected. Finally, 23 formulas that could alleviate AS were correlated to the amelioration of plaques, improvement of plaque stability, modification of lipid level and lipid metabolism, and the effects of anti-inflammation and antioxidant stress with multiple components and targets. However, the methodological quality was low and incomplete among the included literature. Conclusions . Thus, taken together, the studies on postmarketing Chinese patent formulas would provide a novel approach to improve the treatment of AS, and rigorously designed studies would provide high-quality evidence.